Application of Nordic Body Map and Rapid Upper Limb Assessment for Assessing Work-related Musculoskeletal Disorders: A case study in Small and Medium Enterprises - Adiyanto, Okka; Mohamad, Effendi; Jaafar, Rosidah; Ma’ruf, Farid; Faishal, Muhammad; Anggraeni, Anggi (International Journal of Integrated Engineering, 2022)
Musculoskeletal disorder (MSD) is a very common grievance of employees working with SMEs and large industries. It might surface when the posture of the working body is not apt for the task to be carried out. The objective of this research is to examine the risk of MSD for operators in the manufacturing segment of SMEs by deploying two ergonomic approaches: self-report (SR) and observation method (OM). The project has been executed in the manufacturing SMEs in Indonesia. The SR methodology utilises the Nordic Body Map (NBM) for assessing the comfort and grievances of the operator. The OM methodology deploys the Rapid Upper Limb Assessment (RULA) as an appraisal of the worker’s work stance. A Self Report evaluation based on NBM triggered the obtained concerns in the upper body that occur on the back, neck, hips, and buttocks. OM based on RULA assessment observed that the position of worker has a value score of 6, which indicates further analysis and changes are needed at the earliest. Based on the RULA assessment, this paper recommended involvement of ergonomics at the place of work to decrease the MSD issues encountered by the operator and make the places of work relaxing. According to the results, the new workplace registers a value score of 2 based on RULA assessment and this final tally was noted to be a satisfactory posture. Thus, the SR tactic is beneficial for preliminary screening prior to deploying further assessment of the OM methodology. The OM methodology is vital for follow-up assessment so as to use it to offer suggestions on the basis of ergonomic risk evaluation.